Analysis of thin Film Deposition and Defects Influence on Quinoline Derivative-Titanium Dioxide Heterostructure for Potential p-n Junction in Optoelectronic Devices - Oliveira, Natália C. [UNESP]; Fonseca, Lucas P. [UNESP]; Scalvi, Luis V.A. [UNESP] (FapUNIFESP (SciELO), 2024)
Titanium dioxide (TiO2) is an n-type oxide semiconductor, where the electron donors are usually associated with oxygen vacancies and interstitial titanium ions, whereas quinoline derivatives (QD) are usually p-type semiconductors with light emission in the blue range. We report a broad emission band centered at 485 nm, and temperature induced electrical properties of the QD 4-(6-(diethylamino)-4-phenylquinolin-2-yl)benzoic acid and TiO2 films. The combination of QD with TiO2, both layers in the form of thin film, forms a heterostructure in a very convenient format for integration in optoelectronics. Due to the techniques used for film deposition, both sort of films present defects, which are responsible for the electrical characteristics. The dominant level for TiO2 is located about 760 meV from the conduction band bottom, inside the bandgap, whereas for the QD film the activation energy is about 328 meV. Both levels show up for a range above room temperature. In the first case, it suggests the second ionization level of oxygen vacancies (VO2+) or the third ionization level of interstitial titanium ions (Ti3+), considering that both are electron donors, whereas in the case of QD it suggests a mechanism of small polaron tunneling (SPT).When combined as a heterostructure and explored under transport profile perpendicular to the films (transverse contacts) it leads to current-voltage (I-V) rectifying behavior similar to a p-n junction, which is evidence of the p-type-like electrical behavior of the QD, even though this I-V behavior may be destroyed for repetitive I-V measurement, which seems to be related with aging and the presence of defects at the heterostructure interface.
Keywords: Defects; Heterostructure; Organic-inorganic; Quinoline derivative; Titanium dioxide